Kesesuaian Produk Gadai Emas Berdasarkan Fatwa Dewan Syariah Nasional Majelis Ulama Indonesia (DSN-MUI) di Bank Syariah Mandiri Surabaya - Anggia Jancynthia Nurizki Wardhani; Sunan Fanani (Universitas Airlangga, 2015)
This study aims to determine the conformity of contract rahn based Fatwa DSN-MUI at Sharia Mandiri Bank Branch Office Dharmahusada Surabaya. Contract rahn at Sharia Mandiri Bank only be used for products BSM Gold Pawn. The method used is a qualitative approach using case study strategy. The research object is the Sharia Mandiri Bank.Results of this research based on five domains from the mechanism of implementation contract Rahn in Sharia Mandiri Bank Branch Office Dharmahusada Surabaya with Fatwa DSN-MUI. From these domains, there are four domains that have conformity with Fatwa DSNMUI, that was marhun utilization domain, maintenance and storage marhun, sale / auction marhun as well as the cost of Ijarah contract. While in the charge domain on marhun against the costs Ijarah in Sharia Bank Mandiri KCP Dharmahusada don’t have conformity based on Fatwa DSN No.25 / DSN-MUI / III / 2002 the second point number four.